EFEK ANTINEFROTOKSISITAS EKSTRAK ETANOL DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) DENGAN PARAMETER KADAR UREUM TIKUS PUTIH - Sukmawati, Sukmawati; Rahmawati, Rahmawati; Isyanda A., Kenanga (Fakultas Farmasi UMI, 2021)
Nephrotoxicity caused by chemical compounds such as drugs. This condition can cause an increase in urea levels. Antioxidants used to inhibit nephrotoxicity by protect and repair cells. One of the plants as antioxidant is the pandan wangi leaf (Pandanus amaryllifolius Roxb.) which contains phenolic to absorb and neutralize free radicals or decompose peroxides. This study aimed to examine the antinephrotoxicity effect of the ethanolic extract of pandan wangi leaf (Pandanus amaryllifolius Roxb.) on kidney damage with parameters of urea level in rats. Eighteen male Wistar rats were divided into 6 groups. Group 1 as a naive group, group 2 as a negative control by Gentamicin, group 3 as a positive control by amino acid supplement, and groups 4, 5, and 6 were given ethanol extract of pandan wangi leaves at a dose by 125 mg/kgBW, 250 mg/kgBW and 500 mg/kgBW respectively. Nephrotoxicity condition was induced by Gentamicin 100 mg/kgBW (ip) for seven days. The blood samples were taken and measured the serum creatinine levels on days 0, 8th and 21st by Human Analyzer. The results study showed that ethanol extract of pandan wangi leaves at 125 mg/kgBW have the effect as antinephrotoxicity based on decreased ureum levels.